2019
DOI: 10.17776/csj.524612
|View full text |Cite
|
Sign up to set email alerts
|

Ön işlemden geçirilmiş atık arpa kullanarak Rhodobacter sphaeroides O.U.001 ile hidrojen üretimi

Abstract: In the present study, valorization of waste barley by producing hydrogen (H2) and 5-aminolevulinic acid (5-ALA) using Rhodobacter sphaeroides O.U.001 was aimed. Firstly, 3 % (w/v) waste barley hydrolysate was prepared by treating 3 g of powdered waste barley with H2SO4 in a total volume of 100 mL mixture and then autoclaving this mixture at 121 ºC for 30 min. Upon generation of fermentable simple sugars by pretreatment and analytical examination of the hydrolysate in terms of ammonium content, element composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It can be deduced from these results that upon utilization of sugar beet molasses, basic molecules or by-products were produced and they caused an increase in pH of the culture. In the case of using waste barley as feedstock, a different pH profile was attained [11,23] such that the pH of the cultures first dropped below 7 and then climbed back to 7. From these results, it is also confirmed that the type of carbon source and thus the type of metabolism has a determinative effect on the pH.…”
Section: Bacterial Growth and Ph Changes In Culturesmentioning
confidence: 99%
“…It can be deduced from these results that upon utilization of sugar beet molasses, basic molecules or by-products were produced and they caused an increase in pH of the culture. In the case of using waste barley as feedstock, a different pH profile was attained [11,23] such that the pH of the cultures first dropped below 7 and then climbed back to 7. From these results, it is also confirmed that the type of carbon source and thus the type of metabolism has a determinative effect on the pH.…”
Section: Bacterial Growth and Ph Changes In Culturesmentioning
confidence: 99%